Improving Speaking Skills Through Contextual Teaching and Learning Methods in Hyperactive Children in Kindergarten - Wati, Rusni; Suparno, Suparno (Journal of Innovation and Research in Primary Education, 2025)
Early childhood represents a critical period for language development, yet hyperactive children frequently experience significant speaking skill difficulties that hinder their academic and social development. Conventional teaching methods often fail to engage these learners effectively. This Classroom Action Research was conducted at State Kindergarten 2, Busang District, involving 21 hyperactive children aged 4-5 years during the 2024/2025 academic year. The intervention employed Contextual Teaching and Learning methodology through puppet media across three complete cycles, each consisting of two instructional sessions. Data were collected through speaking ability assessments using a validated four-level developmental rubric, systematic observations, interviews, and documentation. Analysis employed descriptive statistics for quantitative data and thematic analysis for qualitative data. Progressive improvement in speaking skills was observed across cycles. Initially, no children achieved advanced proficiency (Developing Very Well), with 62% at Developing as Expected and 38% at Starting to Develop levels. By the final cycle, 58% achieved advanced proficiency, 28% reached expected development, and only 14% remained at the starting level. Qualitative observations revealed enhanced attention, elaborated verbal responses, and improved communicative engagement. Findings demonstrate that CTL methodology effectively addresses the dual challenges of hyperactivity and language development by providing experiential, contextually meaningful learning experiences that align with hyperactive children's learning characteristics, contributing valuable evidence for inclusive early childhood pedagogy.